Broadcast news writing, reporting, and producing - Barnas, Frank (Focal Press, 2013)
Jargon buster: convergent journalism: ?Media convergence is the most significant development in the news industry in the last century. The ability to interchange text, audio, and visual communication over the Internet has fundamentally transformed the way news organizations operate. Convergence has enabled media companies to gather, disseminate, and share information over a variety of platforms. Throughout the history of journalism, it has been common for journalists to study one medium, such as traditional print or broadcast, and to anticipate a career working.